Methods Of Introduction And Acclimatization Of Representatives Of The Family Trichogrammatidae - Jumaev Rasul Axmatovich; Alaviddinkhojayeva Malikakhon Jamoliddin qizi (Emerging Frontiers Library for The American Journal of Agriculture and Biomedical Engineering, 2026)
The article presents scientific research conducted on the introduction and acclimatization of effective species of the Trichogrammatidae family. The study mainly focuses on the introduction and acclimatization of the species Trichogramma ostriniae. This species is considered an effective parasitic entomophage of representatives of the order Leoidoptera occurring in the maize agrobiocenosis. In the conducted research, trichogramma species were introduced and acclimatized under biolaboratory conditions. During the acclimatization process, scientific studies were carried out on feeding, reproduction, and storage of trichogramma. When breeding trichogramma in the biolaboratory, 65% relative humidity and an air temperature of +27-280C were maintained. It was determined that the introduced Trichogramma ostriniae produced 8 generations per year under biolaboratory conditions.